The Queue System Optimization on Motorcycle Service Based on Aspiration Level Model (Case Study of Workshop Ahass Handayani Motor (1706) Semarag) - Oktaviyanty, Hetty; Dwidayati, Nur Karomah; Agoestanto, Arief (Universitas Negeri Semarang, 2018)
The purpose of this research is to determine the optimal number of server by using queuing system based on aspiration level model at Ahass Handayani Motor (1706) Semarang workshop. In general, queues arise due to service needs that exceed the capacity and service facilities available. Therefore, to provide excellent service for customers, required an optimal service system. The study was conducted by taking primary data for two days in rush hour. The results obtained, the queue system at the workshop Ahass Handayani Motor (1706) Semarang using FIFO queue discipline with 6 servers. The arrival time distribution is the poisson distribution and the service time distribution is the exponential distribution. So we get the queue model (M / M / 6) :( GD / âˆž / âˆž). Based on the aspiration level model, the queuing model in the workshop of Ahass Handayani Motor (1706) Semarang is optimal with 6 servers. With condition: 1) customer does not wait more than 2 hours to be served, 2) server idle time not more than 10 minutes. Size of server effectiveness is said to be optimal because it has an average waiting time in the system for 1.6361 hours on May 22, 2017 with a percentage of idle time of the waiters 7,5947% and the average waiting time in the system for 2.01 hours on the 23rd May 2017 with the percentage of unemployed servants 7,2188%.